THE INFLUENCED FACTORS ON THE SYPHILIS DISEASE INFECTION MATTER ON THE MAN PRODUCTIVE AGE IN THE TELADAN PUBLIC HEALTH CENTER MEDAN PERIOD OF JANUARY – SEPTEMBER 2019 - Liana Rosa; Rahayu Lubis; Heru Santoso (State Islamic University of North Sumatra Indonesia, 2020)
Syphilis is an STI that is caused by Treponema pallidum, mainly transmitted through sexual contact. Men of childbearing age (25-49 years) are at high risk of contracting syphilis due to sexual activity. The purpose of this study was to analyze the factors that influence the occurrence of syphilis in men of productive age. This research is an observational analytic study with case control design. The study was conducted at the Medan Exemplary Health Center. The study population was all VCT clinic visitors from January 2019 to September 2019. The number of case samples was 59 people, and control samples were 59. Data analysis used univariate analysis, bivariate analysis with chi-square, and multivariate analysis using multiple logistic regression tests. The results showed that the factors that influenced syphilis were syphilis history (p = 0.013), condom use (p = 0.012), and number of sexual partners (p = 0.003), while education variables (p = 0.222), injecting drug use (p = 0.585) and the sex of the spouse has no effect. The most dominant variable influencing the occurrence of syphilis in men of productive age (25-49 years) in Puskesmas Teladan Medan is the history of syphilis / STI. Men of childbearing age who have a history of syphilis / STI have a 15.6 times higher chance of developing syphilis compared to men with no history of syphilis / STI. It is recommended to the Medan Exemplary Health Center to provide health education through counseling about syphilis and ways to prevent it. Keywords: Syphilis, Male, Productive Age